2011
DOI: 10.3109/00365521.2011.551887
|View full text |Cite
|
Sign up to set email alerts
|

Increase of regulatory T cells in ileal mucosa of untreated pediatric Crohn's disease patients

Abstract: Mucosal numbers of Foxp3(+) Tregs and activated (CD25+) macrophages are elevated in both pediatric and adult ileal CD. The greater increase of ileal Foxp3+ Tregs in pediatric CD than in adult CD might contribute to the relatively less frequent phenotype of isolated ileal enteritis in CD children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 45 publications
1
25
2
3
Order By: Relevance
“…We observed elevated numbers of F4/80+ cells and FoxP3+ cells in the cecum of AIEC-colonized mice, the latter of which were virtually absent from AIEC-naïve mice. Mucosal FoxP3+ Tregs and activated macrophages are also elevated in pediatric and adult CD 36 , which seems to be a response specific to CD and not ulcerative colitis 37 . TGF-β regulates the development of FoxP3+ cells in CD that correlates with response to anti-TNF infliximab therapy 38 .…”
Section: Discussionmentioning
confidence: 89%
“…We observed elevated numbers of F4/80+ cells and FoxP3+ cells in the cecum of AIEC-colonized mice, the latter of which were virtually absent from AIEC-naïve mice. Mucosal FoxP3+ Tregs and activated macrophages are also elevated in pediatric and adult CD 36 , which seems to be a response specific to CD and not ulcerative colitis 37 . TGF-β regulates the development of FoxP3+ cells in CD that correlates with response to anti-TNF infliximab therapy 38 .…”
Section: Discussionmentioning
confidence: 89%
“…Compared to adults, there is an overrepresentation of CD over UC in pediatric patients, while UC is often more severe in children compared to adults [14]. There are several lines of evidence for strong disease-related correlation patterns with the gut microbiota in children [15].…”
Section: Introductionmentioning
confidence: 99%
“… 38 found that although both Crohn’s disease and ulcerative colitis patients had decreased Treg populations in the peripheral blood during active disease, Treg numbers in intestinal tissue biopsies were not substantially different from those in patients with other inflammatory diseases. Other studies corroborate these results, and in most cases show a consistent expansion of Tregs in both inflamed and non‐inflamed sections of the gut in adult and paediatric patients with IBD 39–41 . Notably, the majority of these studies did not take into consideration the possibility that FoxP3 expression can also identify activated effector T cells 42 or the possibility that FoxP3‐expressing cells can trans‐differentiate into inflammatory cytokine producing cells that may or may not retain their suppressive function 43 .…”
Section: Are Tregs Dysfunctional In Ibd?mentioning
confidence: 91%